Internationalization of National Postal Operators: Developing and Strengthening Positions in Traditional and New Networks - Toteva, Kalina (Research Papers, 2019)
Taking into account the increasing economic integration and diversification of international market players, the study aims to identify the underlying characteristic of national postal operators’ participation in international business. The author creates a basic model regarding their participation, and identifies the operators’ administrative heritage as a key factor for its establishment. This heritage is a result of operators’ involvement in two networks (traditional) with strong positions of the state – the system of state institutions and the global postal network. Using established models for environmental analysis the author identifies the macro, meso and microlevel factors that have the greatest impact on the development of the basic model. They create opportunities for extending the process of internationalization by entering new networks. The main conclusion of the study is that national postal operators’ participation in international business is an interorganizational phenomenon – it is based on the interaction with various organizations in traditional and new networks and developing positions. The contribution of the study is that it integrates knowledge from the fields of international business and management into postal sector’s business practices, which helps to explain the foundations of operators’ internationalization. It formulates for the first time the basic model, and outlines the factors that determine it.
Keywords: International business; National postal operators; Factors of the international business environment; State owned enterprises; Internationalization